Effects of vaccination against reproductive diseases on reproductive performance of beef cows submitted to fixed-timed AI in Brazilian cow-calf operations - Aono, F. H. [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Alfieri, A. A.; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier, 2013)
The objectives were to assess incidence of pregnancy losses, associate this outcome with immunization programs against reproductive diseases, and evaluate the effects of vaccination against bovine herpesvirus-1 (BoHV-1), bovine viral diarrhea virus (BVDV), and Leptospira spp., on reproductive efficiency of Brazilian cow-calf operations. In experiment 1, 7614 lactating Nelore cows from 18 ranches were assigned to the same estrus synchronization and fixed-time AI protocol (ESFTAI; Days -11 to 0). Pregnancy status was determined with transrectal ultrasonography on Days 30 and 120 after AI. Pregnancy loss was deemed to have occurred when cows were pregnant on Day 30 but nonpregnant on Day 120. Incidence of pregnancy loss across all ranches was 4.1%; pregnancy losses were detected (P < 0.10) in 14 ranches but not detected (P > 0.11) in four ranches. Pregnancy loss was lower (P ≤ 0.02) in ranches that vaccinated against BoHV-1, BVDV, and Leptospira spp. compared with ranches that did not vaccinate, or only vaccinated against Leptospira spp. In experiments 2 and 3, lactating Nelore cows (N = 1950 and 2793, respectively) from ranches that did not have a history of vaccinating against reproductive diseases (experiment 2), or only vaccinated against Leptospira spp. (experiment 3), were assigned to the same ESFTAI used in experiment 1. Within each ranch, cows received (VAC) or not (CON) vaccination against BoHV-1, BVDV, and Leptospira spp. at the beginning of the ESFTAI (Day -11) and 30 days after (Day 41) AI. In experiment 2, VAC cows had greater (P ≤ 0.05) pregnancy rates compared with CON on Days 30 and 120. In experiments 2 and 3, pregnancy loss was reduced (P ≤ 0.03) in primiparous VAC cows compared with CON cohorts. In experiment 4, 367 primiparous, lactating Nelore cows previously vaccinated against Leptospira spp. were assigned to the same ESFTAI used in experiment 1. Cows received VAC, or the same vaccine 30 days before (Day -41) and at the beginning (Day -11) of the ESFTAI (PREVAC). Pregnancy rates on Days 30 and 120 were greater (P ≤ 0.05) in PREVAC cows compared with VAC cows. In conclusion, pregnancy losses affected reproductive and overall efficiency of Brazilian cow-calf operations, and might be directly associated with BoHV-1, BVDV, and Leptospira spp. infections. Hence, vaccinating cows against these pathogens, particularly when both doses are administered before fixed-time AI, improved reproductive performance in Brazilian cow-calf systems. © 2013 Elsevier Inc.
Keywords: Beef cows; Reproductive diseases; Reproductive performance; Vaccine; animal; animal disease; artificial insemination; body composition; Bovine diarrhea virus; Bovine herpes virus; bovine viral diarrhea; cattle; cattle disease; female; herpes virus infection; immunology; Leptospira; leptospirosis; physiology; pregnancy; reproduction; vaccination; veterinary abortion; Abortion, Veterinary; Animals; Body Composition; Bovine Virus Diarrhea-Mucosal Disease; Cattle; Cattle Diseases; Diarrhea Viruses, Bovine Viral; Female; Herpesviridae Infections; Herpesvirus 1, Bovine; Insemination, Artificial; Leptospirosis; Pregnancy; Reproduction; Vaccination; Bovinae; Bovine herpesvirus 1; Bovine viral diarrhea virus 1; Human herpesvirus 1